Efecto de niveles de gallinaza aplicado como materia organica en la producción de·maíz amarillo duro (zea mazs ), en un suelo ultisol de Aucaloma - San Martín - Bernales del Aguila, Carlos Ivan (1995)
With the finally objetive to fine the gallinaza levels effect as a source of Organic Matter on the yielding of corn Marginal 28-T over ultisols and to determine an economic analysis; we realized an experiment located on Aucaloma a small- settelment, Distrtict of San Roque de Cumbaza, province of Lamas; with franco arenoso, pH 4.8, phosphorous available zero (0) ppm, Organic Hatter 2,8%, Ca-Mg 2.5 meq/100 gr soi l. We used the Complete Block Randomizado design. The issves we got shows the level of yielding per Kg/Ha witness (T1) shows statistic meaning wit 175,.8 Kg/Ha (or Kg/Ha the gallinaza), at one at the same time, most yielding we got was with (T6) 1360..6 Kg/H ( 23 ton/Ha the gallinaza). Since an economic point witness (T3) is who shows the best' yielding 1012,.5 Kg/Ha (14 ton/Ha the gallinaza), variables costs were stabilitied from (T4). We concluded that, to the conditions for this work. is advisable to continue with the research of this nature on corn, with growing quantities of gallinaza, to orient the yielding evaluations during two or more periods, in order to watch posterior profits of RFB an gallinaza